The Selection of Best Open Source Integrated Library Management Software: A Review - AL-Kubaisy, Wijdan Jaber; Al-Khateeb, Belal (Iraqi Journal of Science, 2024)
Since the first established library in the 7th century B.C., libraries have played a main role in civilization development due to their ability to help humans reach the required information easily. However, in the last decades, after the huge propagation of information from various sources, including the addition of books, other data types such as audio, video, and images have emerged. Therefore, finding an integrated system to manage this huge amount of library data became necessary. As a result, the integrated library system (ILS) improved its efficiency and ability to manage various and enormous amounts of data in addition to following the lending processes and inventory management. There are many commercial and open-source integrated systems used in libraries; selecting the best open-source integrated library system to achieve the library requirements is still challenging due to the variety of available libraries. Although these libraries are open source and freely available, the installation process requires a long time and expert effort, making selecting the best library system a sensitive and important mission. This survey demonstrates the most famous open-source integrated library systems and the essential technologies used to build them, along with the system specifications, to help librarians and educational and academic institutions select the best one for their requirements. Through reviewing the previous academic research, it was noticed that many of them had the task of selecting the right ILS, but most of them did not handle the programming principles based on it, which is the milestone in its building, so we recommended using an automated technique to evaluate ILS and select the best one.